Antibiotic Sensitivities of Bacteria Isolated from Children with Urinary Tract Infections - Gürgöze, Metin Kaya; Doğan, Yaşar; Kizirgil, Ahmet; Toraman, Zülal Aşçi; Aygün, Denizmen (Fırat University, 2002)
Aim: One of the most common causes of renal failure in children is urinary tract infections. Early detection of these cases have great significance to prevent for occurring of renal parenchymal injury. In this study we aimed to determine causative agents and their antibiotic susceptibility in children with urinary tract infection. Material and Methods: In this study, 176 patients diagnosed with urinary tract infection between April and December in 2000 were included. There were 105 female (60%), 71 male (40%) cases and mean age was 3.08±2.05 year. Midstream urine samples were taken from patient and then cultured. Results: The most common microorganism isolated was E. coli (57%). Resistance development was assesed with antibiotic susceptibility test results. It was observed that there was high resistance to oral antibiotics including ampicillin, ampicillin-sulbactam, amoxycillin-clavulanic acid, co-trimoxazole and cefuroxime that commonly administered in the treatment of urinary tract infections Conclusions: Even if the commonly used antibiotic were given as initial therapy, the treatment must be reevaluated according to antibiotic susceptibility test results since resistance is high for those agents. In addition, long-term follow-up and frequent visits of cases will be an appropriate way of handling in urinary tract infections.

Amaç: Çocuklarda böbrek yetmezliğinin en sık görülen nedenlerinden biri idrar yolu enfeksiyonlarıdır. Bu olguların erken tanı ve tedavisi böbrek parankim hasarının önlenmesinde önem taşımaktadır. Bu çalışmada idrar yolu enfeksiyonlu çocuklarda etken patojenlerin ve antibiyotik duyarlılıklarının saptanması amaçlandı. Gereç ve Yöntem: Nisan 2000- Aralık 2000 ayları arasında idrar yolu enfeksiyonu tanısı konulan 176 hasta çalışmaya alındı. Olguların 105'i (%60) kız, 71'i (%40) erkek ve yaş ortalaması 3.08±2.05 yıl idi. Hastalardan orta akım idrar örnekleri alınarak kültürleri yapıldı. Bulgular: İdrar kültüründe en sık üreyen mikroorganizmanın Escherichia coli (%57) olduğu görüldü. Antibiyotik duyarlılık testi sonuçlarına göre tedavide sık kullanılan ampisilin, ampisilin/sulbaktam, amoksisilin/klavulanik asit, ko-trimoksazol ve sefuroksim gibi oral antibiyotiklere karşı direnç gelişiminin yüksek oranlarda olduğu gözlendi. Sonuç: Tedavide sık kullanılan oral antibiyotiklere karşı direncin yüksek olması nedeni ile, başlangıç tedavisi olarak bu antibiyotikler kullanılsa bile antibiyotik duyarlılık testi sonucuna göre tedavi planı yeniden gözden geçirilmelidir. Ayrıca uygun tedavi sonrası, olguların sık aralıklarla uzun süreli izlemi önem taşımaktadır.
İdrar Yolu Enfeksiyonlu Çocuklardan İzole Edilen Bakterilerin Çeşitli Antibiyotiklere Duyarlılıkları